Physico-Chemical Methods for Determination of Lard in Food Products for Halal Authentication Study - A. Rohman; Y.B Che Man (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2008)
Food authenticity is a great concern not only for consumers but also for food producers. Lard and pork are prohibitedto be consumed by followers of Islamic religion. Lard and pork intakes are associated with several health problems. Because of the restriction reasons to consume lard and pork and its biological implications, indeed, analytical methods offering fast and reliable methods are required. This article will describe some physico-chemical methods i.e. Fou- rier transform infrared (FTIR) spectroscopy, chromatography, electronic nose, and differential scanning calorimetry (DSC) used to analyze the presence of lard and pork in food products.